Compositional and Functional Considerations for Bovine-, Caprine- and Plant-Based Infant Formulas - Margaret E. Byrne; James A. O’Mahony; Tom F. O’Callaghan (Dairy, 2021)
Breastmilk is the optimal source of nutrition for infants. However, in circumstances where breastfeeding is not possible or feasible, infant formula provides an essential alternative to fulfil the nutritional requirements of the developing infant. Traditionally, the manufacture of infant formula has involved utilisation of bovine milk as a base ingredient, formulated with other nutrients and bioactive ingredients to closely match the composition of human breastmilk. While it is the most widely available type of formula on the market, bovine-based infant formula is not suitable for all infants, and therefore alternatives such as those based on caprine milk, soy and rice protein are becoming increasingly available. This review provides a detailed examination of the composition of infant formula prepared from bovine milk, caprine milk, soy, and rice protein sources. Available literature on nutrient bio-accessibility and aspects of protein functionality relevant to infant formula is discussed.